Kedudukan Perempuan dalam Hadis: (Kajian atas Buku Buya Hamka Berbicara tentang Perempuan) - Muhammad Royyan Faqih Azhary (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2024)
This study examines the views of Haji Abdul Malik Karim Amrullah (Buya Hamka) on the status of women in hadith, as presented in his book Buya Hamka Berbicara tentang Perempuan (Buya Hamka Talks About Women). This book was published during the formulation of the Indonesian Marriage Law of 1973, making it part of Buya Hamka’s efforts to defend and honor women in an Islamic framework. Based on this background, this study focuses on two main research questions: first, how does Buya Hamka interpret the status of women in the context of hadith as discussed in his book? Second, how does he understand women's virtues and roles in marriage from the perspective of hadith?This research employs content analysis with a qualitative approach, gathering data from books, classical hadith collections, and relevant literature. The primary source is Buya Hamka Berbicara tentang Perempuan, supplemented by hadith compilations, journal articles, and other supporting references. The findings indicate that Buya Hamka views Islam as granting women an esteemed and dignified position in various aspects of life, particularly in marriage. The Qur’an and hadith provide not only gender equity in many aspects but also special recognition of women’s roles, affirming their vital contributions to family and society. Therefore, Buya Hamka’s interpretation underscores that Islam not only upholds women’s dignity but also grants them fair and proportional rights in accordance with Islamic teachings.